2002
DOI: 10.1038/sj.jhh.1001354
|View full text |Cite
|
Sign up to set email alerts
|

Diuretics in the treatment of patients who present congestive heart failure and hypertension

Abstract: The main operational objective of diuretic therapy in patients who present congestive heart failure and hypertension is to reduce or to suppress excess bodily fluid. Effective diuretic therapy decreases cardiac size when the heart is dilated, and it reduces lung congestion and excess water. Consequently, external respiratory work diminishes and cardiac output would be redistributed in favour of systemic vascular beds other than that of the respiratory muscles; dyspnoea decreases markedly and there is a slight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…2002). In addition, Reyes (2002) found that diuretics may improve the symptoms of hypertension, heart enlargement and pleural effusion, thereby decreasing the workload of respiratory muscles and relieving difficulty with breathing and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2002). In addition, Reyes (2002) found that diuretics may improve the symptoms of hypertension, heart enlargement and pleural effusion, thereby decreasing the workload of respiratory muscles and relieving difficulty with breathing and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of diuretic therapy on fatigue may be explained by its contribution to increased frequency of urination and urgency, loss of sleep because of disrupted sleep patterns and early awakening and electrolyte imbalance (Bennett et al 2000, Nohria et al 2002. In addition, Reyes (2002) found that diuretics may improve the symptoms of hypertension, heart enlargement and pleural effusion, thereby decreasing the workload of respiratory muscles and relieving difficulty with breathing and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Cough, a well-known class effect of ACE inhibitors, is less frequent with PER than with other drugs in this class, and it can be mitigated by the addition of a CCB, such as AML [ 59 ]. PER reduces AML-induced oedema [ 60 ] and it can correct kaliuresis induced by diuretics, such as IND [ 61 ]. Consistent with these counterbalancing actions, PER/IND/AML is associated with low incidences of cough and oedema, and these AEs are easily manageable.…”
Section: What Is the Current Clinical Position Of Per/ind/aml?mentioning
confidence: 99%